"Delete Your Account": The 2016 Presidential Race on Twitter. (August 2018) - Evans, Heather K.; Brown, Kayla J.; Wimberly, Tiffany
While there has been a growth in the number of published studies about how candidates for the U.S. House and Senate use Twitter, candidates for president have been largely ignored. In this article, we examine the way the two 2016 presidential candidates communicated on Twitter. Using a content analysis of all tweets sent from Hillary Clinton and Donald Trump's accounts from July 1 to Election Day, we explore whether the two candidates used this social network in the same ways, stressed similar policy issues, and were equally likely to "go negative" online.